2010
DOI: 10.1016/j.jinorgbio.2010.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Control of reduction thermodynamics in [2Fe–2S] ferredoxins

Abstract: The reaction thermodynamics for the one-electron reduction of the [2Fe-2S] cluster of both human ferredoxin and various surface point mutants, in which each of the negatively charged residues Asp72, Glu73, Asp76, and Asp79 were converted to Ala, have been determined by variable temperature spectroelectrochemical measurements. The above are conserved residues that have been implicated in interactions between the vertebrate-type ferredoxins and their redox partners. In all cases, and similar to other 2Fe-ferredo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Such a compensatory effect has been thoroughly described for several events in biomolecules and has been the subject of several theories and controversies. 18,20,74,76,77,133,146,[150][151][152][153][154][155][156][157][158][159][160][161][162][163][164] For redox processes involving metal centers in proteins it can be considered the hallmark of the reduction-induced reorganization of the hydrogen bonding network within the hydration sphere of the molecule. 20,74,76,77,133,146,[150][151][152]162,[165][166][167] The linear DH 0 rc versus TDS 0 rc plots at 293 K for both mutants at different urea concentrations are reported in Fig.…”
Section: Voltammetric Responsementioning
confidence: 99%
“…Such a compensatory effect has been thoroughly described for several events in biomolecules and has been the subject of several theories and controversies. 18,20,74,76,77,133,146,[150][151][152][153][154][155][156][157][158][159][160][161][162][163][164] For redox processes involving metal centers in proteins it can be considered the hallmark of the reduction-induced reorganization of the hydrogen bonding network within the hydration sphere of the molecule. 20,74,76,77,133,146,[150][151][152]162,[165][166][167] The linear DH 0 rc versus TDS 0 rc plots at 293 K for both mutants at different urea concentrations are reported in Fig.…”
Section: Voltammetric Responsementioning
confidence: 99%
“…The immobilization-induced changes in the reduction thermodynamics for the HP heme (yielding signal I) (Table 1) are much larger that of the corresponding change in E1 0 . As shown elsewhere, 12,[48][49][50] this compensatory behavior is most likely the result of changes in the reduction-induced reorganization of water molecules in the hydration sphere of the molecule following interaction with the SAM. The moderate decrease in E1 0 is consistent with the electrostatic effect of the negative charge of the SAM which would stabilize the more positively charged oxidized state of the heme, as observed for monoheme cytochrome c immobilized on the same SAM.…”
Section: Redox Properties Of Immobilized Sb-dhcmentioning
confidence: 63%
“…These values have been shown to originate from the intrinsic coordinative properties of the cluster, which favor the oxidized state, and to be subject to fine-tuning by the interactions between the cluster and the protein environment [20]. As noted elsewhere [21], the compensatory enthalpy and entropy changes within this protein family (evidenced by the significantly lower variations in ΔG°’ rc relative to ΔH°’ rc and ΔS°’ rc ) indicate that these terms are contributed mainly by reduction-induced solvent reorganization effects. Under these conditions it can be shown that, to a first approximation, the ΔG°’ rc values correspond to the protein-based enthalpic changes, which include bonding and nonbonding interactions that result in the selective stabilization of one of the two oxidation states (the oxidized state in this case) [22].…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, the factors controlling ΔG°’ rc , and therefore E°’ , are likely to be similar for Sp etp Fd and Hs Fd, consistent with the similarity in CD spectral patterns observed for these two proteins in the near-UV and visible regions, which show only minor differences in the 300 nm to 440 nm range. The much lower reduction potentials for Hs Fd, relative to adrenodoxin has been ascribed, by analogy with plant-type ferredoxins, both to a less polar and less solvent exposed cluster environment and to the lack of a hydrogen bond between a labile sulfide of the cluster and the imidazole of a nearby histidine residue (His56 in Hs Fd) which in the case of adrenodoxin stabilizes the more negatively charged reduced Fe 2 S 2 (Cys) 4 center [21, 23–25]. This argument most likely applies to Sp etp Fd as well.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation